Centro Restaurativo El Buen Pastor (2020)
The project comes from the understanding of restorative justice, how it works in Colombia, its phases, and its goals. The aim is to define how should architectural design serve justice. In this case, we use the specific case of an all-woman prison in Bogotá (Cárcel El Buen Pastor). We try to understand the need of three main users: the victim, the victimizer, and the community. We intend to create through architecture activities and relationships for dialogue and second chances.